IMPLEMENTASI PELAKSANAAN LAYANAN PENEMPATAN DAN PENYALURAN SMA NEGERI 2 TARAKAN TAHUN AJARAN 2017-2018 - Faris Faris; Hendra Pribadi; Urotul Aliyah (Jurnal Bimbingan dan Konseling Borneo, 2019)
This Research was to find out how the implementation of placement and the distribution of SMA Negeri 2 Tarakan year 2017-2018. Explain how the implementation of placement and distribution services. This study was conducted with a subject of counseling teacher. The techniques of collecting data were conducted in-depth interviews, observation and documentation. Data analysis techniques Were data reduction, data display, and conclusion. Then analyzed by using technique of data validity. The results showed that the implementation of placement service and distribution of SMA Negeri 2 Tarakan Year Teaching Year 2017/2018 implemented in accordance with the program that has been made.  Keywords: Implementation of Placement service and Distributio